Face Processing in Early Development: A Systematic Review of Behavioral Studies and Considerations in Times of COVID-19 Pandemic - Carnevali, Laura; Gui, Anna; Jones, Emily J. H.; Farroni, Teresa (Frontiers in Psychology, 2022)
Human faces are one of the most prominent stimuli infants in the visual environment of young infants and convey critical information for the development of social cognition. During the COVID-19 pandemic, mask wearing has become a common practice outside the home environment. With masks covering nose and mouth regions, the facial cues available to the infant are impoverished. The impact of these changes on development is unknown, but is critical to debates around mask mandates in early childhood settings. As infants grow, they increasingly interact with a broader range of familiar and unfamiliar people outside the home; in these settings, mask wearing could possibly influence social development. In order to generate hypotheses about the effects of mask wearing on infant social development, in the present work we systematically review N=129 studies selected based on the most recent PRISMA guidelines providing a state-of-the-art framework of behavioural studies investigating face processing in early infancy. We focused on identifying sensitive periods during which being exposed to specific facial features or to the entire face configuration has been found to be important for the development of perceptive and socio-communicative skills. For perceptive skills, infants gradually learn to analyze the eyes or the gaze direction within the context of the entire face configuration. This contributes to identity recognition as well as emotional expression discrimination. For socio-communicative skills, direct gaze and emotional facial expressions are crucial for attention engagement while eye-gaze cuing is important for joint attention. Moreover, attention to the mouth is particularly relevant for speech learning. We discuss possible implications of the exposure to masked faces for developmental needs and functions. Providing groundwork for further research, we encourage the investigation of the consequences of mask-wearing for infants’ perceptive and socio-communicative development, suggesting new directions within the research field.